Perancangan Sistem Pencatatan Akuntansi dan Pelaporan Keuangan Pada Rumah Makan Gorengan Kamput - Mangapul Siahaan; Ariq Bimantoro (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Information technology has experienced very fast development at this time. Rumah Makan Gorengan Kamput is one of the SME’s in the city of Batam, during operation they still use manual accounting and financial reporting records. This community service (PkM) is expected to be able to provide support to SME Rumah Makan Gorengan Kamput. The author uses the PHP programming language and the waterfall method to complete the system with several stages such as requirements analysis, design, development, testing, implementation. The final result of this research is a website application that will be used by business owners to help their business activities.